PREPARATION AND CHARACTERIZATION OF CELLULOSE ACETATE (CA)/KIT-6 MIXED MATRIX MEMBRANE - PATRICK TUNAGI, SWORO (IRC, 2017)
Separation by membrane has been extensively studied due to its fast and energy efficient process that does not need a phase change. Inorganic and organic membranes are the two types of membranes that have been used in the membrane separation industry for long. However, due to their shortcomings. Mixed matrix membrane (MMM) is a new class of membrane that combines both organic and inorganic properties to form a membrane with high selectivity, permeability, good thermal and mechanical properties, and economically friendly. In this project, KIT-6 mesoporous silica was incorporated into cellulose acetate (CA) matrix to form KIT-6/CA MMM. Top solution of cellulose acetate (CA) polymer was prepared by dissolving CA in tetrahydrofuran solvent. KIT-6 filler particles were then added to the homogenous solution of CA polymer in different loading of 0 wt%, 2 wt%, 4 wt%, 6 wt%, 8 wt%, and 10 wt%, to form the solution. The solution was casted on petri disc to form MMMs. The effect of KIT-6 loading on the formation of the MMMs was investigated. The formed membranes were characterized using Fourier transform infrared (FTIR) spectroscopy, scanning electronic microscopy (SEM), X-Ray diffractions, and thermogravimetric analyser (TGA) for its properties